The degree of practice of the directors of education in the province of Irbid for strategic planning from the point of view of the heads of administrative and technical departments - Hamaydeh, Ola Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2017)
This study aimed at defining the degree of practice of the Education directors of Irbid for the skills of strategic planning from the point of view of heads of administrative and technical departments, and to indicate the effect of variables: gender, experience and scientific qualification on the degree of practicing strategic planning among the directors of education. The sample of the study consisted of all members of the original study society, and they are the heads of the administrative and technical departments in the directorates of education in Irbid Governorate, which are (160) individuals for the academic year 2016/2017. To achieve the objectives of the study, the study used the descriptive method by applying a questionnaire consisting of (40) paragraphs distributed evenly on the five strategic planning areas. The results of the study showed that the managers of the education practice strategic planning skills in the performance of their work in the middle of the assessment, but they are interested in some The results showed that there were no statistically significant differences at the level of significance ( 0.05 0.05) between the average scores of the sample of the study sample attributed to the sex variables and the scientific qualification. However, there were statistically significant differences at the mean level ( 0.05 0.05) between mean Grades study sample attributed to a variable number of years of experience in the head of the department and for department heads experienced (11 years and over.